2019
DOI: 10.1016/j.epsl.2019.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Radiogenic isotopes document the start of subduction in the Western Pacific

Abstract: Subduction initiation is one of the least understood aspects of plate tectonics. In an effort to obtain the first in situ magmatic record of subduction initiation, the International Ocean Discovery Program Expedition 352 drilled at four sites in the inner trench wall of the Bonin Trench to recover 1.22 km of oceanic upper crust accreted within a few m.y. of subduction initiation. The two sites nearer to the trench (U1440 and U1441) yielded axial and off-axis fore-arc basalts (FAB), while those c. 15 km further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
122
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(142 citation statements)
references
References 46 publications
13
122
0
Order By: Relevance
“…By comparing the formation models of the initiation of subduction in the IBM system (Li et al, ; Reagan et al, ), a model for subduction initiation in the Meilaotewula intra‐oceanic arc during the late Carboniferous to early Permian can be deduced (Figure ). Late Carboniferous intra‐oceanic subduction initiation in the southeastern PAO began along a transform fault or fracture zone (Figure a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the formation models of the initiation of subduction in the IBM system (Li et al, ; Reagan et al, ), a model for subduction initiation in the Meilaotewula intra‐oceanic arc during the late Carboniferous to early Permian can be deduced (Figure ). Late Carboniferous intra‐oceanic subduction initiation in the southeastern PAO began along a transform fault or fracture zone (Figure a).…”
Section: Discussionmentioning
confidence: 99%
“…Evolution of the late Carboniferous to early Permian Meilaotewula intra‐oceanic forearc system in central Inner Mongolia, based on the subduction infancy model (Li et al, ; Reagan et al, ; Whattam & Stern, ). The region may record initiation of subduction in the southeastern PAO.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the Suhaylah Village section, it has long been held that Geotimes locally tops the volcanic sequence, being directly overlain by Suhaylah Formation sediments, and therefore that the Alley strata are discontinuous (Fleet and Robertson, 1980;Lippard et al, 1986). However, the presence of Geotimes at the top of this section was apparently not confirmed by geochemical analyses.…”
Section: Lateral Continuity Of the Alley Unitmentioning
confidence: 98%
“…The first regional-scale geological map of the Semail ophiolite with a differentiated lower and upper extrusive sequence was compiled by Lippard et al (1986) at a scale of 1 : 250 000. This work was expanded upon by the 1 : 50 000 and 1 : 100 000 maps produced by Japanese and French teams together with the Ministry of Petroleum and Minerals (BME, 1987a, b, c;BRGM, 1986aBRGM, , b, 1993a.…”
Section: Previous Geological Mapsmentioning
confidence: 99%
“…Based on isotopic compositions, Li et al (2018) found that LSB and HSB magmas are likely mixtures between a melt generated from a variably depleted Indian mantle source, and at least 2 with depleted mantle to produce LSB is likely derived from Pacific oceanic crust . In a similar manner, a mixing relationship between the residual mantle (post-LSB extraction) and a component derived from Pacific pelagic sediment was used to show that HSB likely involve melting sediment in addition to melting of basaltic crust .…”
Section: Trace Element Variation and Petrogenetic Implicationsmentioning
confidence: 99%